Exploring Mixed Reality for Patient Education in Cerebral Angiograms: A Pilot Study - Murdock, Paul; Bonthu, Snehita; Chavez, Angel; Ooi, Yinn Cher (Applied Clinical Informatics, 2025)
Cerebral aneurysms (CAs) affect 3 to 5% of the general population, with saccular aneurysms being the most common type. Despite advances in treatment, patient understanding of CAs and associated procedures remains limited, impacting informed consent and treatment outcomes.This pilot study aims to evaluate the effectiveness of mixed reality (MR) technology in enhancing patient education and understanding of cerebral angiograms and aneurysm treatment, thereby improving the patient–surgeon communication process.A nonrandomized single-center prospective study was conducted with 16 patients diagnosed with intracranial aneurysms. Participants used a Microsoft HoloLens to view an interactive 3D presentation about cerebral angiograms and aneurysm treatments. Pre- and post-intervention surveys assessed their knowledge and anxiety levels using a 5-point Likert scale. The Wilcoxon's signed-rank test was used for statistical analysis.Post-intervention, the total survey scores improved significantly (average increase of 6.7 points, p < 0.05). Seven out of eight survey questions showed significant knowledge improvement. The mean perceived ability to explain aneurysm treatment improved by 1.38 points and understanding of access points for procedures increased by 1.31 points (both p < 0.05). The question regarding understanding of treatment risks did not show significant change (p > 0.05). Anxiety levels decreased, with 75% of participants reporting reduced anxiety post-intervention.MR technology significantly enhances patient understanding and reduces anxiety regarding cerebral angiogram procedures and aneurysm treatments. These findings support the integration of MR in patient education to improve clinical outcomes and patient satisfaction. This approach offers a promising direction for future health care communication strategies, especially in complex procedures requiring detailed patient comprehension.
Keywords: mixed reality; patient satisfaction; shared decision making; surgical visualization; intracranial aneurysm